If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4s + -1 = 8 + -2 Reorder the terms: -1 + 4s = 8 + -2 Combine like terms: 8 + -2 = 6 -1 + 4s = 6 Solving -1 + 4s = 6 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 4s = 6 + 1 Combine like terms: -1 + 1 = 0 0 + 4s = 6 + 1 4s = 6 + 1 Combine like terms: 6 + 1 = 7 4s = 7 Divide each side by '4'. s = 1.75 Simplifying s = 1.75
| 50-5x=3x+18 | | 4n-8=n | | 6x+9=x | | 6a+2a-3=21 | | p^2+5p+4=0 | | 2x+37=10x-43 | | 8y-2y^2=6 | | 3[2a+7]=3a+12 | | Y=15y+28 | | 17-3x=2x+8 | | 7x+21= | | 2a+5ab-7a-18b= | | 234x-(345x-334)=3456 | | 7aX-3b= | | 4x^2+9x-15=0 | | 2x*4x= | | x^2+x-7=y | | 28t^2=3k-(5k*7t) | | 3x^2-3x-2=166 | | X-5+8-2x=34-3x+23 | | x^3= | | 45=4d-7 | | 16=4x+(3x-4) | | 4-7*45=x | | 16=4x+(3x+4) | | x(6x+7)=5 | | 1080=14(0.6x)+12(0.3x)+0(0.1x) | | C=14(0.6*1080)+12(0.3*1080)+0(0.1*1080) | | C=14(0.6x)+12(0.3x)+0(0.1x) | | 7-4*3+0+1=x | | 5x+11=69 | | 7-4*3+0+1= |